Zebrafish Primordial Germ Cell Migration - Aalto, Anne; Olguin-Olguin, Adan; Raz, Erez (Frontiers in Cell and Developmental Biology, 2021)
Similar to many other organisms, zebrafish primordial germ cells (PGCs) are specified at a location distinct from that of gonadal somatic cells. Guided by chemotactic cues PGCs migrate through embryonic tissues towards the region where the gonad develops. In this process, PGCs employ a bleb-driven amoeboid migration mode, characterized by low adhesion and high actomyosin contractility, a strategy used by other migrating cells, such as leukocytes and certain types of cancer cells. The mechanisms underlying the motility and the directed migration of PGCs should be robust to ensure arrival at the target, thereby contributing to the fertility of the organism. These features make PGCs an excellent model for studying guided single-cell migration in vivo. In this review, we present recent findings regarding the establishment and maintenance of cell polarity that are essential for motility and discuss the mechanisms by which cell polarization and directed migration are controlled by chemical and physical cues.